Progress in Periodontal Surgery: Advancing from Debridement to Functional Regeneration - Wang, Dan (International Journal of Public Health and Medical Research, 2025)
Periodontal surgery is the core treatment for moderate to severe periodontitis, aiming to control infection, eliminate periodontal pockets, and restore periodontal tissue function. Over the past decade, driven by the integration of digital medicine, tissue engineering, and minimally invasive technology, periodontal surgery has achieved a paradigm shift from "disease control" to "functional regeneration". This systematic review summarizes the latest progress in periodontal surgery, focusing on digital diagnosis and navigation, minimally invasive debridement techniques, periodontal regenerative therapy, and aesthetic periodontal surgery. We also analyze current clinical challenges and future development directions to provide evidence-based support for periodontal clinical practice. A comprehensive literature search was conducted in PubMed, Embase, and Cochrane Library using keywords including "periodontal surgery", "minimally invasive periodontal therapy", "periodontal regeneration", and "digital periodontology". Relevant studies published between 2018 and 2025 were included, and the final analysis covered 40 high-quality articles (randomized controlled trials, systematic reviews, and prospective cohort studies).